ADMINISTRATIVE SYSTEM OF INTER-CITY BUS TICKET BOOKING - INTER-PROVINCE (AKAP) AT THE PO. XYZ CIPUTAT BY USING MICROSOFT VISUAL BASIC 6.0 - Dimas Wisnu Aryadi; Ir. Fitri Sjafrina, MM (Jurnal Sistem Informasi, 2009)
This paper describes the writing on the ticket reservation system at PO adeministrasi.XYZ Ciputat that during this process is done manually. Therefore the writer create aticket reservation system administration using a computerized system using MicrosoftVisual Basic 6.0 and Databases using Microsoft Access. Hopefully this writing hasbecome an alternative for a company or to its employees who expect all theiractivities are operating effectively, efficiently and coordinated.